If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 7 = 5(5 + -9) Reorder the terms: 7 + -3x = 5(5 + -9) Combine like terms: 5 + -9 = -4 7 + -3x = 5(-4) Multiply 5 * -4 7 + -3x = -20 Solving 7 + -3x = -20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3x = -20 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = -20 + -7 -3x = -20 + -7 Combine like terms: -20 + -7 = -27 -3x = -27 Divide each side by '-3'. x = 9 Simplifying x = 9
| -(7)-(6y)=13 | | F(x)=2x-6whenf(-1) | | 3/4x=-27/3/4 | | Ln(x-2)+ln(x+2)=5 | | 7/10-3/4 | | 4x-8/x-2=4 | | 12x+32=1+52x | | 2In(x-1)+30=34 | | 2(1+8a)= | | x-8/x-4=2 | | ln(3x+1)=1 | | 4r-5=r-2 | | 2sin(x)cos(x)+2=0 | | 1/2(3)-3 | | 10(4-10x)= | | x^2-32x+177=0 | | 8x+4=12x-24 | | 100-15x+40x=300 | | t+(-110)=263 | | 4n+2a=2n | | .45x+.95y=.75 | | 8/15=5/x | | 6x-5=8x+12 | | x=18/2/5 | | x^2+4cx+4=0 | | .3ax=6 | | 8(2p+4)= | | 8(4+2x)= | | x/7=3/14 | | 8x=8x+20 | | -2x-1=3x+5/2 | | -4(-8x+12)=-26-32x |